خطاب الكراهية في نطاق الفقه واجتهادات المحاكم الجنائية الدولية - نعمة, احمد عبيس (Journal of Legal Sciences, 2017)
The Article will examine the position of Hate Speech in international criminal law, within two sections: the first one shed light on the linguistic and terminological concept of term of Hate Speech, as well as looks at hate speech effects in scope of the periods of war and peace.The second section will focus on Hate Speech and whether occupied to the ranks of abnormal and criminal behaviors, in the two sub-sections: first looks at the legal qualification (the level of national and regional efforts), while the second will search on International Criminal Courts Jurisprudences, so as to answer the following question: what is the reason of differences treatment of Hate Speech in Statutes of International Criminal Courts? Why some of them adopted Hate Speech as a Criminal behavior in itself, while the other tended to adapt it as a non- dependency crime in itself.